The Influence of Spirituality on Stress and Subjective Well-Being: A study on healthcare professionals in India (International Journal of Food and Nutritional Sciences, 2022)
Healthcare workers often work in high-stress environments where they experience extreme stress, emotional weariness, and burnout. These conditions can hurt their overall quality of life and subjective well-being (SWB). Taking into account spirituality as a multifaceted concept that includes a sense of meaning, purpose, and connection to something more than oneself, this study investigates the function of spirituality in reducing stress and improving SWB among healthcare professionals. Utilising a combination of qualitative and quantitative data from a sample of healthcare professionals with varying specialisations, this study explores how spiritual practices, beliefs, and experiences support resilience against stressful work environments and aid in stress reduction. According to the research, there is a substantial correlation between higher degrees of spirituality and lower perceived stress levels as well as higher SWB, which is reflected in better mental health outcomes, life satisfaction, and emotional control. The study also emphasises how crucial it is to incorporate spiritual care into healthcare environments to promote staff members' well-being and, ultimately, improve patient care. These findings highlight the necessity for healthcare organisations to acknowledge spirituality as a useful tool for encouraging employees' overall well-being.